[PP.18.08] INFLUENCE OF FIXED-DOSE COMBINATION PERINDOPRIL/AMLODIPINE ON TARGET ORGAN DAMAGE IN PATIENTS WITH ARTERIAL HYPERTENSION AND ISCHEMIC HEART DISEASE. (September 2016) - Radchenko, G.; Mushtenko, L.; Torbas, O.; Kushnir, S.; Sirenko, Y.
Abstract : Objective: To evaluate the antihypertensive effectiveness and changes of target organ damage in patients with arterial hypertension (AH) and ischemic heart disease (IHD) on fixed dose combination (FDC) (perindopril(P)|amlodipin(A)) treatment. Design and method: There were included 27 patients (age > 30 yrs, untreated hypertensives with verified IHD without myocardial infarction history and BP > 160/100 and <200/120 mmHg or who were on monotherapy (except P), but their office BP was >140/90 and <200/120 mmHg, ), whom were evaluated office systolic (SBP) and diastolic (DBP) blood pressure (BP), 24-h SBP and 24-h DBP, central SBP (cSBP) and aorta pulse wave velocity (PWV) by Sphygmocor, EchoCG with Tissue Doppler, albuminuria, intima-media thickness (IMT), ankle-brachial index (ABI), biochemical blood analysis. Follow-up period was 12 mths. After wash-out period P|A administered in dose 5|5 mg with up-titration to 10|10 mg every 2 weeks. Indapamide was added as the third drug. Beta-blockers (96.3%) or alpha-blockers were allowed for better BP control and IHD treatment. Primary end-points were BP lowering (office, systolic, central), significant (>SD) dynamic of target organ damage signs, tolerance of FDC. Results: Baseline FDC were administered to 30 pts, but all data were collected at this time only in 27 pts. Office SBP|DBP decreased from 151.2 ± 2.8|92.3 ± 2.7 till 133.3 ± 1.8|77.2 ± 1.4 mmHg(p < 0.001|0.001), 24-hSBP|DBP from 138.2 ± 2.0|85.4 ± 2.7 till 118.8 ± 1.3|73.2 ± 1.2 mmHg(p < 0.001|0.001), cSBP from 139.8 ± 2.1 till 116.3 ± 2.8 mmHg(p < 0.001). Target BP was achieved in all patients. Effective BP control followed by positive target organ changes (tab:^-p < 0.001, ^^-p < 0.05). The changes of E|E' and albuminuria did not correlate with office BP lowering, but with aorta cSBP and PWV decreasing. We did not note any significant changes of biochemical patterns, except LDL-C decreasing, that was due to intensive statin therapy. Figure. No caption available. Conclusions: The treatment based on FDC (P|A) was effective not only in decreasing of office and ambulatory BP, but central SBP too. It led to decreasing of target organ damage. Diastolic left ventricular function and renal damage improving were connected with much decreasing of cSBP and arterial stiffness.